Dimensi Budaya Hofstede dalam Komunikasi Antarkaryawan Organisasi Multinasional - Girsang, Anastasia Putri Pearlyn; Murtiningsih, Bertha Sri Eko; Astagini, Nuria (Calathu: Jurnal Ilmu Komunikasi, 2024)
The cultural differences within an organization can create various barriers in the communication process among employees. Therefore, with the increasing number of international migrants in Indonesia, employees are required to enhance their understanding of cross-cultural communication. One example is the marketing department employees of a multinational organization under the initial DO, which is led by two managers from different countries, Indonesia and Germany. Hence, this research aims to examine the communication practices of DO’s marketing department, which are influenced by two vastly contrasting cultures using Hofstede's cultural dimensions. To conduct the research, a descriptive case study method was used, employing in-depth interviews with five members of DO's marketing department. The research found that the dynamics of communication in the marketing department are greatly influenced by cultural dimensions, particularly in aspects such as decision-making and discussion processes, communication styles, task distribution patterns, freedom for innovation, employee work patterns, views on deadlines, and views on employee rights such as leave and dress code. The research also found that members of the department from Indonesia will only adopt foreign cultures brought by their expatriate leaders if they are deemed suitable or compatible with their own culture. Conversely, if they are not compatible, the German leader tends to accommodate and adjust to their other members. Understanding cultural dynamics that happens in communication among employees allows the company to detect types of communications that are happening and detect problems that might happen, for a more effective process. Keywords: employee communication, Germany, Hofstede’s cultural dimensions, Indonesia, multinational organization